Cooperatives for Forest Management and Marketing of Timber Products - Dalvi, M. K. (Indian Forester, 1960)
In 1947, on attammg the independence, the then Chief Minister of Bombay State, Shri B. G. Kher, introduced on an experimental basis the execution of forest contracts and marketing of the resultant produce through Cooperative Societies formed of the forest labourers as a part of the comprehensive programme launched for an all round advancement of the Adiwasis. The objective underlying this experiment was to see that the Adiwasi forest labourers who reside in and around the State forest areas, not only get fair wages for the hard work put in by it in the remote, difficult and unhealthy areas, but also get the profits out of lumbering contracts, which otherwise, so far was the monopoly of the individual contractors acting as middle men, thus, increasing the earnings and consequently raising the economic standard of the forest labourers. It is also expected that, because of profits earned by the Adiwasi forest labourers, they would look upon forests as their milking cow, and not enemy as has been the case hitherto, resulting in better protection of forests and good cooperation from them in implementing the development programme of the forest wealth of the State. Though at present because of the extreme illiteracy in forest labour, these cooperatives which are purely democratic institutions, are managed with necessary help from the recognised social service or anisations, it is expected that in due course they will be managed by the labourers themselves, grooming them into a democratic way of life.